Evaluation of Methodologies for Compensation of Out of Plane Motions in a 2D Digital Image Correlation Setup. (20th August 2015) - Wittevrongel, L.; Badaloni, M.; Balcaen, R.; Lava, P.; Debruyne, D.
Abstract In 2D digital image correlation, out of plane motions are an important experimental factor to consider. Because a 2D setup does not provide any depth information, movements towards the camera (out of plane motions) are disadvantageous for the surface measurement. The effects of out of plane motions in a 2D digital image correlation (DIC) setup have been investigated profoundly in previous works. The compensation of these motions however is less investigated. Therefore, this paper will handle on solutions for correcting or minimising out of plane motions in 2D DIC measurements. Three compensation methods are implemented and validated. Firstly, a mechanical camera positioning tool is developed to avoid misalignments of the camera and therefore avoid most of the out of plane motions. Secondly, the camera is aligned numerically using the camera pinhole model and numerically deforming the images. Finally, a method proposed in literature using a region of compensation is used in this validation. All three methods have shown to be able to minimise out of plane motions. Validated in an experimental setup, a great improvement of the identified Poisson ratio is observed during multiple tensile tests.